Ecological Approach in Managing the Technology of Oil Refineries - Myasnikova, Olga Yuryevna; Lysytska, Svetlana Mayorovna; Shcherbakova, Natalya Sergeevna; Shamsheev, Sergey Vladimirovich; Spitsyna, Tatiana Andreevna; Kubasova, Elena Ivanovna (International Journal of Energy Economics and Policy, 2019)
The paper aims to analyze the problem of the complexity in managing of the environmental safety of an oil refinery. The possibility of using environmental monitoring methods for integrated regulation and the formation of optimal control parameters is noted. It's based on the principles of combining efficient production processes with environmental programs, which will be promotive of the production output with the technogenic impact minimization of oil refining technology on the environment. Keywords: environmental management, environmental safety, management parameters at a refinery, oil refinery. JEL Classifications: L71, Q35 DOI: https://doi.org/10.32479/ijeep.7734